Electrochemical investigations of layered materials for energy applications - Tan, Shu Min (2017)
For sustainable and continuous growth of our society, moving away from fossil fuel-driven economy and towards renewable energy sources production is critical. Energy-related electrochemical processes such as hydrogen evolution and oxygen reduction reactions (HER and ORR respectively) have the potential to achieve a “Hydrogen Economy” which is based on hydrogen as the energy carrier. However, the current best-performing HER and ORR electrocatalysts are based on Pt whose scarcity and exorbitant cost limit its industrial use. Consequently, this thesis endeavoured investigations into graphene and transition metal dichalcogenides (TMDs) as potential alternatives to the Pt electrode. Examinations of the impurities inherent to graphene revealed their impacts on the electrochemical and electrocatalytic properties of graphene. Through employing centimetre-sized molybdenite crystals, the edge planes have been established to constitute the active sites for HER activity beyond reasonable doubt. With regards to the fabrication of TMD and related hybrids, fresh insight into the conventional chemical exfoliation of TMDs via the use of novel aromatic-based organolithium intercalants has been acquired. Moreover, the innovative electrochemical depositions of TMD and related hybrids have also engendered new perception of such synthesis methods as potential principle fabrication approach to TMDs as highly active electrocatalysts. The efforts invested into the current work have culminated in the development of green fabrication procedures toward high-performance electrocatalysts, which differentiates this work from prior literature that focuses on the activity rather than environmental impacts of their fabrication. These findings would accelerate the onset of an economy supported by truly sustainable energy sources.